Natural Killer Cell Engagers (NKCEs): a new frontier in cancer immunotherapy - Zhang, Minchuan; Lam, Kong-Peng; Xu, Shengli (Frontiers in Immunology, 2023)
Natural Killer (NK) cells are a type of innate lymphoid cells that play a crucial role in immunity by killing virally infected or tumor cells and secreting cytokines and chemokines. NK cell-mediated immunotherapy has emerged as a promising approach for cancer treatment due to its safety and effectiveness. NK cell engagers (NKCEs), such as BiKE (bispecific killer cell engager) or TriKE (trispecific killer cell engager), are a novel class of antibody-based therapeutics that exhibit several advantages over other cancer immunotherapies harnessing NK cells. By bridging NK and tumor cells, NKCEs activate NK cells and lead to tumor cell lysis. A growing number of NKCEs are currently undergoing development, with some already in clinical trials. However, there is a need for more comprehensive studies to determine how the molecular design of NKCEs affects their functionality and manufacturability, which are crucial for their development as off-the-shelf drugs for cancer treatment. In this review, we summarize current knowledge on NKCE development and discuss critical factors required for the production of effective NKCEs.